Validating the Construct of Environmental Attitude in Urban Nepal Using the Two-Dimensional Model of Ecological Values - Shakil Regmi; Bruce Johnson (Urban Science)
The Two-Dimensional Model of Ecological Values (2-MEV) explores the environmental values and attitudes of adolescents, typically 11–16 years old. The 2-MEV has two higher-order factors (values), Preservation and Utilisation, and primary factors (attitudes) under each value. The 2-MEV Scale has been validated in several industrialised countries, showing a negative but weak to moderate correlation between the two values. When in a previous study the scale was tested in rural Nepal, a non-industrialised country, the relationship between the two values was also negative but much stronger. The aim of the present study was to test this unusual relationship using the scale in urban Nepal. Five hundred forty-seven adolescents responded to the 25 items, which were reduced to 19 items after exploratory and confirmatory factor analyses. The model used in the urban setting resulted in a weak, negative corelation between the two values, which is similar to the structure that has been found in industrialised countries. However, the characteristics of environmental attitudes of adolescents in urban Nepal showed a strong similarity to the characteristics found in the previous study in rural Nepal. Therefore, the construct or structure of environmental attitude does not appear to be dependent on the socioeconomic status of a country/community. The results also showed slightly higher pro-environmental attitudes in adolescents in the urban community compared to the rural community of Nepal.